Between Conformism and Innovativeness . From Studies on Students’ Stragies - Przyborowska, Beata; Murawska, Iwona (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The presented text aims at answering the question what strategies the youth use nowadays in order to adapt to school and to the role of a student. In the present research Merton’s theory on deviance was used. The text presents the results of a study which shows the two most often used by students strategies: conformism and innovativeness. The study was conducted with the use of the quantitative strategy, in a comparative diagram and the method used was surveys. It was done on a representative group of 656 students. The presented analysis is a part of bigger research on middle-schoolers’ student strategies.